A Feasibility study on the Integrated Telecommunications System - Calumba, Ma. Isabel; Mueco, Francis Lee; Tablante, Rinna; Tanesa, Hayley; Tecson, Ma. Regina (College of Engineering, 1998)
The Integrated Telecommunications System (ITS) is an intra-office telecommunication system that seamlessly merges locally developed software and hardware technologies. The ITS provides an intelligent and efficient office communication and messaging solution intended for small to medium sized organizations. the system incorporates innovative features and useful applications that promote staff productivity and efficiency enabling a business to cope with increasing customer demand for quality and service. Among these applications are voice mail, message notification by call back, auto reminder and Web access of voice mail. The ITS utilizes CTI technology to automate and add value to the communication process of an organization. This offers clients and personnel a full range of efficient, convenient and cost effective around-the-clock services.